2004
DOI: 10.1093/toxsci/kfh174
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Xenoestrogen-Contaminated Fish during Lactation Alters Adult Male Reproductive Function

Abstract: Little information exists on the transfer of endocrine-disrupting effects through the food chain. The transfer of chemicals, particularly from the aquatic ecosystem, that can cause such effects on fish-eating predators must be established. Fish from the St. Lawrence River are exposed to xenoestrogens causing male reproductive dysfunction. The objective of this study was to determine if lactational exposure to contaminated fish could alter the development of the male reproductive system in rats. Three experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Through these actions environmental estrogens affect vertebrate reproduction across a wide range of doses causing reduced fertility and fecundity, altered reproductive behavior, gonad morphological changes, and decreased embryonic survival (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Although both sexes are affected, males exhibit the highest degree and number of detrimental effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Through these actions environmental estrogens affect vertebrate reproduction across a wide range of doses causing reduced fertility and fecundity, altered reproductive behavior, gonad morphological changes, and decreased embryonic survival (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Although both sexes are affected, males exhibit the highest degree and number of detrimental effects.…”
mentioning
confidence: 99%
“…Although both sexes are affected, males exhibit the highest degree and number of detrimental effects. Specific male defects caused by environmental estrogen exposures in vertebrates include: intersex (25,29), diminished sperm count (27,(35)(36)(37), genital tract alterations (38), increased germ cell apoptosis (30,33), and male induced embryonic mortality (31,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4b). Histological analyses of the testes of these fish indicate that almost 35 % of fish captured near sewage outfall exhibit intersex (Aravindakshan et al 2004a). Spermatogenesis requires coordinated intercellular communication, as mediated by gap junctions shown to be essential for spermatogenesis in the mammalian testis.…”
Section: Endocrine Disruption In Fishmentioning
confidence: 99%
“…In a more extensive study, spottail shiners were shown to be exposed to environmental estrogens in the SLR. This contamination begins approximately 20 km upstream from the Island of Montreal, and although it results from several inputs including the Ottawa River, sewage effluents from Montreal contribute the greatest charge in estrogenic compounds (Sabik et al 2004;Aravindakshan et al 2004a). Male spottail shiners captured near the WWTP discharge point exhibit elevated levels of VTG and altered reproductive functions, including delayed spermatogenesis, decreased sperm counts, altered sperm motility, and a significantly greater concentration of static sperm (Fig.…”
Section: Endocrine Disruption In Fishmentioning
confidence: 99%